Histomorphometric analysis of external apical root resorption using L-loops and different intrusive forces - Yosuke Miyaji; Hidetoshi Morikuni; Toru Tsujibayashi; Yoshitomo Honda; AKI Nishiura (Clinical and Investigative Orthodontics)
Purpose This study aimed to conduct a histomorphometric analysis on the impact of varying intrusive forces on external apical root resorption (EARR) in rat molars, using an L-loop was employed to apply intrusion forces, artificially inducing EARR in the maxillary left first molar (M1) of rats.Materials and methods The L-loop was bent on a plaster rat model using stainless steel round wires with diameters of 0.014 and 0.016 inches. Using a universal test force measuring device, L-loops were calibrated to 4 N/mm and 6 N/mm for the 0.014-inch and 0.016-inch diameter stainless steel round wires, respectively. Fifteen-week-old Sprague-Dawley (SD) male rats were used and divided into the control (no loop) and experimental (0.014 and 0.016) groups (n = 5 for each group). The L-loop was attached to the left maxillary molar, applying an intrusive force to M1. After 15 days, the rats were euthanized. Maxillary bones were analysed using micro-computed tomography (μCT), evaluating M1 intrusive distance of vertical tooth movement and counting the number of tartrate-resistant acid phosphatase (TRAP)-positive cells on the surface of the mesial root apex and alveolar bone.Results The L-loop groups exhibited significantly increased M1 intrusive distance and TRAP-positive cell counts compared to controls. Specifically, the 0.016 group demonstrated greater M1 intrusive distance and more TRAP-positive cells than the 0.014 group. The M1 intrusive distance and TRAP-positive cells increased when intrusive forces were applied using L-loops of different diameters.Conclusion Greater intrusive forces enhance TRAP-positive cell activity, influencing EARR and vertical tooth movement.